Numerical solutions to systems of fractional Fredholm Integro differential equations, using Chebyshev wavelet method. Issue 5 (3rd September 2018) - Khan, Hassan; Arif, Muhammad; Mohyud-Din, Syed Tauseef; Bushnaq, Samia
ABSTRACT: The Chebyshev Wavelet Method (CWM) is applied to evaluate the numerical solutions of some systems of linear fractional Fredholm integro differential equations (FFIDEs). The applicability and validity of the proposed method is ensured by discussing some illustrative examples. The numerical results obtained by this technique are compared with the exact solutions of the problems. The error analysis reveals that the accuracy of the present method is higher than any existing numerical method.